Exposure and risk assessment of urinary trans, trans-Muconic acid in school-age children in the vicinity of a petrochemical complex in Central Taiwan - Cheng, Po-Keng; Ponnusamy, Vinoth Kumar; Prakasham, Karthikeyan; Huang, Hsin-I; Chang, Wan-Ting; Huang, Po-Chin (Frontiers in Public Health, 2023)
School-aged children living near large petrochemical factories may be at high risk of exposure to benzene released during manufacturing processes. We aimed to investigate the urinary concentrations of trans, trans-muconic acid (t,t-MA) in schoolaged children living near a petrochemical complex and to estimate their cumulative risk of benzene exposure. We examined an established cohort (Taiwan Petrochemical Complex Cohort for Children, TPE3C) of school-aged children (aged 6-13 years) who lived near large petrochemical factories in central Taiwan between October 2013 and September 2014. The cohort comprised 297 children from five elementary schools, namely S.-C. Branch (n = 63, school A, 0.9 km), F.-A. (n = 51, school B, 2.7 km), C.-T. (n = 63, school C, 5.5 km), M.-L. (n = 54, school D, 6.9 km), and L.-F.(n = 66, school E, 8.6 km). We analyzed the urinary t,t-MA levels of each participant and estimated their daily intake of benzene. We also performed multiple regression analysis to investigate potential risk factors for a high urinary t,t-MA level in the study cohort. The median urinary t,t-MA levels and median estimated benzene daily intake of the children from each school were as follows: school A, 64.07 ng/mL, 11.13 μg/kg/day; school B, 61.01 ng/mL, 15.32 μg/kg/day; school C, 59.38 ng/mL, 14.81 μg/kg/day; school D, 42.35 ng/mL, 11.67 μg/kg/day; school E, undetected, 0.14 μg/kg/day. The distance between a school and a petrochemical complex (greater 4 distance: β = −0.26, 95% confidence interval [CI] = −0.52 to 0.00, p = 0.053), and the age of the children (older age: β = −3., 95% CI = −5.90 to −1.46, p < 0.001) were identified as potential risk factors. After confounders were adjusted for, the creatinine adjusted urinary t,t-MA levels of the school-age children tended to be lower when the distance between their school and a petrochemical complex was greater.